Hybrid optical fiber-wireless communication to support tactile internet (2019)
5G technologies are systems that will set to change the way people, devices and machines connect. This generation of mobile services provide connection in just one click. The advanced 5G infrastructure, defined as “ubiquitous ultra-broadband network supporting future Internet”, represents a revolution in the telecommunications field. It will enable new secure and reliable services to everyone and everything with ultra-low latency. “Full Immersive Experience”, enriched by “Context Information” and “Anything as a Service” are the main drivers for a substantial adoption of the fifth generation networks [1]. The technical challenges that must be taken into account in the design of the 5G system are many and unprecedented. Therefore,5G is expected to be about 10 times faster than LTE-4G, in addition, it is projected that this network will have100-1000 times higher system capacity, user data rates in the order of Gbps everywhere, 10-100 higher number of connected devices per area, latency in the order of 1 millisecond, and 10 times longer battery life for devices. Due to all these technological changes, for years, researchers, suppliers and manufacturers around the world have studied this new network. In order to transform the user's wireless experience and be able to offer fast generalized connectivity anytime, anywhere, to any device.[2]. All this requires an enabler in the new approach of radio access networks, which could be hybrid optical Fiber-Wireless communications. “Photonics technology has been recognized by the European Union as a Key Enabling Technology (KET), which is a technology that enables a market, many times larger than the market of technology itself”. Photonic techniques have become key enablers to unlock future broadband wireless communications with terabit data rates in order to support the current trends of mobile data traffic[3]. The aim of this thesis is to conceive experimentally and validate 1 millisecond latency hybrid optical Fiber-Wireless access links support for tactile Internet taking into account the system requirements. For this purpose, first a review about the implementation of high-speed data links at 75-110 GHz band with low latency was made. Likewise, this work summarizes the components of hybrid optical Fiber-Wireless communication in W- Band. Second, measurements of the delay contribution from individual elements in the W -Band hybrid system were made. In addition, the main contribution was to develop a procedure for measuring latency physically using software defined radio (SDR) and estimating the overall system latency. In this procedure, potential sources of delay can be identified in current high-data-rate hybrid optical-RF communication systems. After knowing how to measure latency in a hybrid optical Fiber-Wireless system, the following objectives were developed: to test an appropriate multiplexing scheme such as Orthogonal Frequency Division Multiplexing (OFDM), and Generalized Frequency Division Multiplexing (GFDM), to achieve the lowest latency with improved performance; and to implement WDM (Wavelength Division Multiplexing) to achieve the required low latency.